Cultural and Social Capital in the Adaptation of Indonesian Students in the United States - Karim Suryadi; Leni Anggraeni; Fitri Rahmafitria; Ega Prakarsa (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
Research on the adaptation of Indonesian students abroad often emphasizes internal abilities, self-motivation, and various psychological aspects. However, in the study of educational globalization, it is important to reinforce research on internal and psychological aspects with external approaches, such as social and cultural approaches. Therefore, this study measures the cultural and social capital that facilitates the adaptation of Indonesian students in the United States. The research utilized a quantitative approach with multiple linear regression analysis to examine the relationship between variables. The findings indicate that both cultural and social capital have an impact on the adaptation abilities of Indonesian students in the United States, either simultaneously or partially, with social capital showing a more significant influence. The research aims to expand sociological theories related to student adaptation and serves as a strategic study to enhance the adaptation abilities of students studying abroad.